Increased Frequency of Diabetic Ketoacidosis: The Link With COVID-19 Pandemic - d’Annunzio, Giuseppe; Bassi, Marta; De Rose, Elena Lucia; Lezzi, Marilea; Minuto, Nicola; Calevo, Maria Grazia; Gaiero, Alberto; Fichera, Graziella; Borea, Riccardo; Maghnie, Mohamad (Frontiers in Clinical Diabetes and Healthcare, 2022)
Aims Diabetic ketoacidosis is the most severe metabolic derangement due to prolonged insulin deficiency as in type 1 diabetes. Diabetic ketoacidosis, a life-threatening condition, is often diagnosed late. A timely diagnosis is mandatory to prevent its consequences, mainly neurological. The COVID-19 pandemic and lockdown have reduced the availability of medical care and access to hospitals. The aim of our retrospective study was to compare the frequency of ketoacidosis at the diagnosis of type 1 diabetes between the lockdown-post lockdown period and the previous two calendar years, in order to evaluate the impact of the COVID-19 pandemic. Patients and Methods We retrospectively assessed the clinical and metabolic data at the diagnosis of type 1 diabetes in children in the Liguria Region during 3 different time periods: calendar year 2018 (Period A), calendar year 2019 until February 23,2020 (Period B) and from February 24, 2020 onwards to March 31, 2021 (Period C). Results We analyzed 99 patients with newly-diagnosed T1DM from 01/01/2018 to 31/03/2021. Briefly, a younger age at diagnosis of T1DM was observed in Period 2 compared to Period 1 (p = 0.03). The frequency of DKA at clinical onset of T1DM was similar in Period A (32.3%) and Period B (37.5%), while it significantly increased in Period C (61.1%) compared to Period B (37.5%) (p = 0.03). PH values were similar in Period A (7.29 ± 0.14) and Period B (7.27 ± 0.17), while they were significantly lower in Period C (7.21 ± 0.17) compared to Period B (p = 0.04). Conclusions An increase in the frequency of diabetic ketoacidosis has been documented in newly diagnosed pediatric patients in the Liguria Region during and after the lockdown period compared to previous calendar years. This increase could have been caused by the delay in diagnosis following the restrictions imposed by the lockdown with consequently reduced access to health care facilities. More information on the risks of ketoacidosis is desirable by means of social and medical awareness campaigns.